What drives consumer automobile choice? Investigating personality trait predictors of vehicle preference factors. (January 2022) - O'Connor, Peter J.; Moss, Jordan; Adams, Jack; Matemberere, Craig; Kaya, Maria
Abstract: In this study we investigated whether the big five traits and narcissism are associated with consumer preferences for different car features. Using a representative sample of 1000 Australian consumers, we determined the factor structure of a wide range of automobile preferences before exploring their associations with a set of demographic variables, the big five traits (and their facets), and trait narcissism. We found that consumer car preferences reflect two high order dimensions of 'style and performance' (7 sub-factors) and 'safety and practicality' (4 sub-factors) and that numerous demographic variables and personality traits had small to moderate linear relationships with multiple dimensions of automobile preferences. Broadly consistent with a set of hypotheses based on life history theory, we found that consumers who are young, extraverted, and narcissistic tend to value style and performance in automobiles, whereas consumers who are older, agreeable, and conscientious tended to value safety and practicality. While no overt effects of openness were found, different openness facets were associated positively and negatively with style and performance. Highlights: Consumer car preferences can be reduced to factors reflecting performance and safety Men, younger, and more extraverted participants tended to value performance Women, older, and more conscientious participants tended to value safety Those high in narcissism valued both performance and safety